2006
DOI: 10.1002/mrd.20586
|View full text |Cite
|
Sign up to set email alerts
|

The histamine H1 receptor activates the nitric oxide pathway at fertilization

Abstract: Sperm fusion with the egg initiates a signaling cascade that releases intracellular calcium (Ca(i) (2+)) from the endoplasmic reticulum (ER). In sea urchins, Ca(2+) is released as a single, large transient via two distinct pathways. The first depends on inositol 1,4,5-triphosphate (IP(3)) production and triggers the initial phase of Ca(2+) release, while the second depends on nitric oxide (NO) production and is thought to maintain the duration of the Ca(2+) wave. We identified a sea urchin homolog of the seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…In S. purpuratus, HA is an important signalling molecule during fertilization [41]. Antibodies specific to S. purpuratus H1R have shown that this receptor is present in the plasma membrane of the egg, and that activation of the receptor by HA sets off a signaling cascade resulting in intracellular calcium release [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In S. purpuratus, HA is an important signalling molecule during fertilization [41]. Antibodies specific to S. purpuratus H1R have shown that this receptor is present in the plasma membrane of the egg, and that activation of the receptor by HA sets off a signaling cascade resulting in intracellular calcium release [41].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies specific to S. purpuratus H1R have shown that this receptor is present in the plasma membrane of the egg, and that activation of the receptor by HA sets off a signaling cascade resulting in intracellular calcium release [41]. Here we test whether HA acts as a modulator of metamorphic competence by investigating the effects it has on pre-competent larvae.…”
Section: Introductionmentioning
confidence: 99%
“…to histamine suggests induction via an external histamine receptor, which is the expectation for a true metamorphic cue in nature. A sea urchin homologue of the metabotropic histamine H1 receptor of vertebrates (suH1R) has been identified on the surface of Strongylocentrotus purpuratus eggs, and this receptor is an integral part of the Ca2+ release pathway leading to fertilisation (Leguia and Wessel 2006). It is possible that suH1R is expressed in other sea urchins and may be involved in histamine-induced metamorphosis of sea urchin larvae, but this hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A sea urchin homolog of the seven trans-membrane G protein-coupled receptor for histamine (suH 1 R) was recently identified on the cell surface of sea urchin eggs that leads to NO production (Leguia and Wessel, 2006). Treatment of eggs with histamine causes fluctuations in the resting levels of NO in the egg, while antagonists or antibodies of H 1 R inhibit the rise of NO normally observed at fertilization.…”
Section: The Role Of Nitric Oxide and Cyclic Adp Ribose During Fertilmentioning
confidence: 99%